The Unbaptised and the Canonical Process for Declaration of Marriage Nullity - Bartczak, Adam (Prawo Kanoniczne, 2025)
Canon law is the law of the Church community. It forms an internal normative system, with its subjects being baptized individuals who remain in unity with the community. However, the legal norms also extend to other persons. What is the status of an unbaptized person in canon law, and what is their relationship with procedural law? The analysis undertaken provides answers to these questions. The author focuses on highlighting that canon law incorporates the norms of natural 30 A. Bartczak law, which are grounded in human dignity. This is precisely why, although an unbaptized person is not a subject of canon law, they may, based on their natural capacity, be an active participant in a marriage nullity process. In a marriage nullity process, an unbaptized person has all the rights of a party involved in the process, just as a Catholic does. The unbaptized can serve as a witness in the process, and may also act as a procurator or advocate, provided the bishop approves them ad causam. The only instance in which unbaptized individuals do not have rights is within ecclesiastical offices in the ecclesiastical judiciary.